Couplage et adaptation de maillage anisotrope pour des simulations de flux d’air dans des géométries complexes - Dobrzynski, Cécile; Frey, Pascal; Pironneau, Olivier (European Journal of Computational Mechanics, 2007)
The numerical simulation of air flow in a building or a house is certainly a very challenging field of engineering applications. The objectives differ from one application to the other, ranging from the optimization of air conditioning systems in buildings to the study of the propagation of harmful products via the air conditioning system. In this paper, we address the problem of coupling the Navier-Stokes equations for incompressible fluids and a temperature equation. To solve this problem in 3d, we use an anisotropic mesh adaptation strategy. The meshes are generated by a local remeshing techniques based on an anisotropic version of Delaunay kernel. The method is fairly general and applies to other cases as well. We illustrate this problem with an example showing the heating of the last floor of a furnished house.